Social Risk, Fairness Types, and Redistribution - Stefania Bortolotti; Felix Kölle; Ivan Soraperra; Matthias Sutter (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Inequality often arises from strategic interactions among individuals. This is so because risky investments can not only be resolved by chance (natural risk), but also by others' actions (social risk). We study how these different sources of inequality shape fairness judgments and the level of redistribution in a controlled experiment with a total of 2,152 participants. We find significantly less inequality acceptance, and thus much more redistribution, under social risk. In addition to the well-known types of Libertarians, Egalitarians and Choice Egalitarians, we identify a novel, hitherto unnoticed, fairness type — Insurers — who always compensate unlucky risk-takers and are especially prevalent when one is let down by others rather than simply unlucky by chance. This suggests that impartial spectators view betrayal as more deserving of support than bad luck. Our findings show that fairness ideals depend jointly on risk-taking and the way in which risk is resolved, either by nature or another human actor, thus highlighting the important role of strategic interaction for fairness types and redistribution.
Keywords: C91; D63; D90; 330; inequality; fairness views; social risk; redistribution; experiment